4 in 1: Antibody‐free protocol for isolating the main hepatic cells from healthy and cirrhotic single rat livers. Issue 2 (12th November 2018) - Fernández‐Iglesias, Anabel; Ortega‐Ribera, Martí; Guixé‐Muntet, Sergi; Gracia‐Sancho, Jordi
Abstract: Liver cells isolated from pre‐clinical models are essential tools for studying liver (patho)physiology, and also for screening new therapeutic options. We aimed at developing a new antibody‐free isolation method able to obtain the four main hepatic cell types (hepatocytes, liver sinusoidal endothelial cells [LSEC], hepatic macrophages [HMΦ] and hepatic stellate cells [HSC]) from a single rat liver. Control and cirrhotic (CCl4 and TAA) rat livers (n = 6) were perfused, digested with collagenase and mechanically disaggregated obtaining a multicellular suspension. Hepatocytes were purified by low revolution centrifugations while non‐parenchymal cells were subjected to differential centrifugation. Two different fractions were obtained: HSC and mixed LSEC + HMΦ. Further LSEC and HMΦ enrichment was achieved by selective adherence time to collagen‐coated substrates. Isolated cells showed high viability (80%‐95%) and purity (>95%) and were characterized as functional: hepatocytes synthetized albumin and urea, LSEC maintained endocytic capacity and in vivo fenestrae distribution, HMΦ increased expression of inflammatory markers in response to LPS and HSC were activated upon in vitro culture. The 4 in 1 protocol allows the simultaneous isolation of highly pure and functional hepatic cell sub‐populations from control or cirrhotic single livers without antibody selection.